STRATEGI GURU MELALUI METODE TAHQIQ DALAM PENGUATAN HAFALAN AL-QUR’AN SISWA BUMBRUNG SUKSA ISLAMIC BOARDING SCHOOL, THAILAND - Pasaribu, Rahmat; Rahimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze teacher strategies through the tahqiq method in strengthening students’ Qur’an memorization at Bumbrung Suksa Islamic Boarding School, Thailand. The research is based on the importance of teachers’ roles in ensuring the accuracy of Qur’anic recitation, memorization, and comprehension of its meanings. The tahqiq method emphasizes precision in articulation, attention to makhraj, characteristics of letters, and correct application of tajwid through deliberate and reflective reading. This research employed a descriptive qualitative method, with data collected through direct observation and in-depth interviews with Qur’an teachers and school administrators. The data were analyzed inductively through stages of reduction, presentation, and conclusion drawing. The findings indicate that the implementation of the tahqiq method effectively improves students’ memorization quality and recitation accuracy. Supporting factors include teachers’ mastery of tajwid, spiritual guidance, the religious environment of the boarding school, and adequate learning facilities. Meanwhile, inhibiting factors include limited study time, variations in students’ phonetic abilities and memory capacity, as well as language barriers in pronouncing Arabic letters. Overall, the tahqiq method not only enhances Qur’anic memorization but also nurtures Qur’anic character traits such as discipline, patience, and devotion. Therefore, teacher strategies through the tahqiq method serve as an effective and applicable model for improving Qur’an memorization and instilling spiritual values in modern Islamic educational institutions like Bumbrung Suksa Islamic Boarding School, Thailand.